Third Five Year Plan Final Proposals Pondicherry State - Planning Commission (Planning Commission)
On the 1st November 1954, the Administration of the territories constituting the State of Pondicherry was transferred to the Government of India, and the area became reunited with the motherland after 280 years of French rule. From the date of the transfer of the Administration, it has been the effort of the Government of India—be extend to the territories of Pondicherry the benefits of the Development Plans which became available to the rest of the country from the beginning of the First Five Year Plan.
Pondicherry State